Form and Freedom: The Kantian Ethos of Musical Formalism - Appelqvist, Hanne (The Nordic Journal of Aesthetics, 2011)
<!--StartFragment--> Musical formalism is often portrayed as the enemy of artistic freedom. Its main representative, Eduard Hanslick, is seen as a purist who, by emphasizing musical rules, aims at restricting music criticism and even musical practices themselves. It may also seem that formalism is depriving music of its ability to have moral significance, as the semantic connection to the extramusical is denied by the formalistic view. In my paper, I defend formalism by placing Hanslick’s argument in a Kantian framework. It is not hard to find Kantian elements in Hanslick’s work, such as his emphasis on the contemplative and disinterested nature of the aesthetic judgment, the nonconceptuality of music’s content, and his insistence that “beauty has no purpose.” I argue further that Hanslick’s formalism is in fact motivated by and manifests the Kantian conception of freedom as self-legislation. Thus understood, the kind of moral significance music may have rests upon its own autonomous rules. <!--EndFragment-->